NiFe-layered double hydroxide arrays for oxygen evolution reaction in fresh water and seawater. (December 2021) - Dong, Guofa; Xie, Fengyan; Kou, Fangxia; Chen, Tingting; Wang, Fengyun; Zhou, Yingwu; Wu, Kechen; Du, Shaowu; Fang, Ming; Ho, Johnny C.
Abstract: The development of active, durable, and cost-effective electrocatalysts for the oxygen evolution reaction (OER) is crucial for viable hydrogen production from water by electrolysis. In this work, we report a mild, atmospheric pressure-based chemical method for the synthesis of NiFe-containing layered double hydroxide (LDH) nanosheet arrays on a carbon fiber cloth (CC). The obtained NiFe-LDH/CC composites with various Ni/Fe ratios show good performance for OER in alkaline aqueous solutions. Among them, the sample with a Ni/Fe ratio of 6:4 exhibits the best OER activity with overpotential values of only 226 mV in water and 238 mV in seawater at a current density of 10 mA cm −2, which are much lower than those of the benchmarking RuO2 catalyst. The catalytic activity can be maintained for at least 450 h for OER in fresh water and 165 h in seawater at a current density of 100 mA cm −2 . Graphical abstract: Image 1 Highlights: A modified synthesis method was designed for preparing nickel-iron layered double hydroxides (NiFe-LDH). High performance in the electrolysis of fresh water and seawater was achieved using the fabricated NiFe-LDH. High selectivity on oxygen evolution reaction was attained in the seawater splitting.